Feasibility issues impacting optimal levels of maternity care in rural communities: implementing the Rural Birth Index in British Columbia - Jude Kornelsen; Glenys Webster; Stephanie Lin; Nicky Cairncross; Erin Lindstrom; Stefan Grzybowski (BMC, 2023)
Abstract Introduction The continued attrition of maternity services across rural communities in high resource countries demands a rigorous, systematic approach to determining population level need, including a clear understanding of feasibility issues that may constrain achieving and sustaining recommended levels of services. The Rural Birth Index (RBI) proposes a robust and objective methodology to determine such need along with attention to the feasibility of implementation. Background Predictions of appropriate levels of maternity care in rural communities require consideration of the feasibility of implementation. Although previous work has focused on essential considerations that impact feasibility, there is little research documenting the barriers to implementation from the perspective of rural care providers and administrators. Methods We conducted in-depth, qualitative research interviews with rural community health care administrators and providers (n = 14) to understand the challenges of offering maternity care in 10 rural communities across British Columbia (BC). Results Participants articulated three thematic challenges to providing maternity services in their communities: maintaining clinical skills and financial stability in the context of low procedural volume, recruitment and retention of care providers and challenges with patient transport. Conclusions Current models of compensation for maternity care are inadequate and inflexible and underscore many of the challenges to implementing a level of care that is based on population need. Re-thinking provision of care as a social obligation to actualize our system commitment to equity instead of working to achieve economies of scale is the first step to use equitable care. Addressing remuneration will provide the groundwork for solving other barriers to sustainable care.